Identification of myeloid cells in the human enthesis as the main source of local IL-23 production. Issue 7 (24th July 2019) - Bridgewood, Charlie; Watad, Abdulla; Russell, Tobias; Palmer, Timothy M; Marzo-Ortega, Helena; Khan, Almas; Millner, Peter A; Dunsmuir, Robert; Rao, Abhay; Loughenbury, Peter; Wittmann, Miriam; Cuthbert, Richard J; et al.
Abstract : Objective: We investigated whether the normal human spinal enthesis contained resident myeloid cell populations, capable of producing pivotal proinflammatory cytokines including tumour necrosis factor (TNF) and interleukin (IL)-23 and determined whether these could be modified by PDE4 inhibition. Methods: Normal human enthesis soft tissue (ST) and adjacent perientheseal bone (PEB) (n=15) were evaluated using immunohistochemistry (IHC), digested for myeloid cell phenotyping, sorted and stimulated with different adjuvants (lipopolysaccharide and mannan). Stimulated enthesis fractions were analysed for inducible production of spondyloarthropathy disease-relevant mediators (IL-23 full protein, TNF, IL-1β and CCL20). Myeloid populations were also compared with matched blood populations for further mRNA analysis and the effect of PDE4 inhibition was assessed. Results: A myeloid cell population (CD45+ HLADR+ CD14+ CD11c+) phenotype was isolated from both the ST and adjacent PEB and termed 'CD14+ myeloid cells' with tissue localisation confirmed by CD14+ IHC. The CD14− fraction contained a CD123+ HLADR+ CD11c− cell population (plasmacytoid dendritic cells). The CD14+ population was the dominant entheseal producer of IL-23, IL-1β, TNF and CCL20. IL-23 and TNF from the CD14+ population could be downregulated by a PDE4I and other agents (histamine and 8-Bromo-cAMP) which elevate cAMP. Entheseal CD14+ cells had a broadly similar gene expression profile to the corresponding CD14+ population from matched blood but showed significantly lower CCR2 gene expression. Conclusions: The human enthesis contains a CD14+ myeloid population that produces most of the inducible IL-23, IL-1β, TNF and CCL20. This population has similar gene expression profile to the matched blood CD14+ population.